2019
DOI: 10.4314/acsj.v27i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Estimates for heritability and consumer-validation of a penetrometer method for phenotyping softness of cooked cassava roots

Abstract: Although breeders have made significant progress in the genetic improvement of cassava (Manihot esculenta Crantz) for agronomic traits, lack of information on heritability and limited testing of highthroughput phenotyping methods are major limitations to improving root quality traits, such as softness after cooking, which rank high among Ugandan consumers. The objectives of this study were to determine heritability for softness of cooked cassava roots, and quantify the relationship between penetrometer and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Currently, efforts are devoted towards development of reproducible methods for measuring attributes with appreciable genetic variation in our cassava breeding populations. The first priority is softness of boiled roots that we propose to measure using near infra‐red spectroscopy (NIRS), all leveraging on previous work (Iragaba et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, efforts are devoted towards development of reproducible methods for measuring attributes with appreciable genetic variation in our cassava breeding populations. The first priority is softness of boiled roots that we propose to measure using near infra‐red spectroscopy (NIRS), all leveraging on previous work (Iragaba et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the developed descriptors could be used in developing more robust and high‐throughput phenotyping technologies such as use of near infra‐red spectroscopy (NIRS). Previous studies have indicated that consumer‐testing and sensory evaluation results can have high correlations with instrument characterisation (Padonou et al ., 2005; Iragaba et al ., 2019). Additionally, sensory descriptors developed in this study could be used by breeders in assessing the quality of the cassava breeding lines before they are released to the end users.…”
Section: Resultsmentioning
confidence: 99%
“…Large variation in the time required for roots to get soft in response to boiling has been reported and linked to genetic and environmental factors (Pereira et al ., 1985; Fukuda & Borges, 1988; Borges et al ., 2002; Beleia et al ., 2004; Azevedo Miranda et al ., 2008; Sajeev et al ., 2010; Talma et al ., 2013; Iragaba et al ., 2019). Cooking time (CT) tends to be shorter in plants harvested at a younger age (Lorenzi, 1994; Ngeve, 2003; Chirif, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Routine assessment of cooking quality, including CT, should be performed in breeding for varieties targeting the market for boiled cassava (Dixon et al ., 1994; Iragaba et al ., 2019). This is a requirement to increase the likelihood of adoption of improved genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype discovery and calling was done jointly on 1,530 samples: in addition to the 556 new samples collected for this study, 624 samples described by Iragaba et al. (2019) were included as well as a random set of 350 samples that were selected from a diverse panel of breeding lines at NaCRRI (Kayondo et al., 2018). The single‐end raw reads of 150 bp were processed through the TASSEL GBS v2 production pipeline (Glaubitz et al., 2014).…”
Section: Methodsmentioning
confidence: 99%